Network and Revenue Analysis of an Affiliate Marketing Program in the Travel Industry - Rolim, Lucas L.; Simões, Jefferson E.; Figueiredo, Daniel R. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2020)
The widespread adoption of e-commerce over the past two decades has transformed businesses and sparked novel marketing strategies. In affiliate marketing individuals sign up with companies to promote or sell their products in independent venues such as blogs and channels controlled by the affiliate, receiving compensations for their actions. This work analyzes Clube Hurb, a real and large affiliate marketing program, considering the affiliate network structure, the revenue generated by affiliates, and their relationship. While the network is largely fragmented (90.7% of the affiliates are isolated) and most affiliates never sell (99.5%), different network and revenue statistics exhibit heavy-tailed behavior and are sometimes correlated. The findings shed light on affiliate marketing dynamics and can drive future studies to improve performance.